MODEL KECELAKAAN SEPEDA MOTOR PADA SUATU RUAS JALAN - Suraji, Aji; Sulistio, Harnen (Jurnal Transportasi, 2010)
Recently, motorcycle population in Indonesia is increasing rapidly. Meanwhile, the number of accidents involving motorcycles is higher than that of other motor vehicles. Based on the problem, it is important to find out a solution so that the road transportation safety can be created. The objective of this study is to model motorcycle accidents on the road. The dependent variable, as a response variable, is the number of motorcycle accidents and the independent variables are traffic volume, speed, lane width, lane number, and shoulder. The road accident data were collected from 18 roads in four areas, including Surabaya City, Malang City, Malang Regency, and Batu City. Modeling analysis employed a Generalized Linear Modeling (GLM) method. The results indicated that the model can be used to describe the actual condition of the road accidents. Moreover, it is also showed that the motorcycle accidents are significantly influenced by volume, speed, lane width, lane number, and shoulder variables. High volume and speed will increase accident risks, but the increase in lane width, lane number, and shoulder will decrease accident risks.Keywords: motorcycle accident, motorcycle accident modeling, road traffic accident